Differences in plasma metabolomics between sows fed dl-methionine and its hydroxy analogue reveal a strong association of milk composition and neonatal growth with maternal methionine nutrition. Issue 4 (2nd February 2015) - Zhang, Xiaoling; Li, Hao; Liu, Guangmang; Wan, Haifeng; Mercier, Yves; Wu, Caimei; Wu, Xiuqun; Che, Lianqiang; Lin, Yan; Xu, Shengyu; Tian, Gang; Chen, Daiwen; et al.
Abstract : The aim of the present study was to determine whether increased consumption of methionine asdl -methionine (DLM) or its hydroxy analoguedl -2-hydroxy-4-methylthiobutanoic acid (HMTBA) could benefit milk synthesis and neonatal growth. For this purpose, eighteen cross-bred (Landrace × Yorkshire) primiparous sows were fed a control (CON), DLM or HMTBA diet ( n 6 per diet) from 0 to 14 d post-partum. At postnatal day 14, piglets in the HMTBA group had higher body weight ( P = 0·02) than those in the CON group, tended ( P = 0·07) to be higher than those in the DLM group, and had higher ( P < 0·05) mRNA abundance of jejunal fatty acid-binding protein 2, intestinal than those in the CON and DLM groups. Compared with the CON diet-fed sows, milk protein, non-fat solid, and lysine, histidine and ornithine concentrations decreased in the DLM diet-fed sows ( P < 0·05), and milk fat, lactose, and cysteine and taurine concentrations increased in the HMTBA diet-fed sows ( P < 0·05). Plasma homocysteine and urea N concentrations that averaged across time were increased ( P < 0·05) in sows fed the DLM diet compared with those fed the CON diet. Metabolomic results based on 1 H NMR spectroscopy revealed that consumption of the HMTBA and DLM diets increased ( P < 0·05) both sow plasma methionine and valine levels; however, consumption of the DLM diet led to lower ( P < 0·05) plasma levels of lysine, tyrosine, glucose and acetate and higher ( P < 0·05) plasma levels of citrate, lactate, formate, glycerol, myo -inositol and N -acetyl glycoprotein in sows. Collectively, neonatal growth and milk synthesis were regulated by dietary methionine levels and sources, which resulted in marked alterations in amino acid, lipid and glycogen metabolism.